2015
DOI: 10.1556/achrom.27.2015.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Specific RP-HPLC Method for the Estimation of γ-Aminobutyric Acid in Rat Brain Tissue Samples Using Benzoyl Chloride Derivatization and PDA Detection

Abstract: Summary.A new, rapid, and specific reversed phase high-performance liquid chromatographic (RP-HPLC) method involving precolumn derivatization with benzoyl chloride was developed and validated for the estimation of γ-aminobutyric acid (GABA) in rat brain tissue preparations. The derivatization product of GABA was identified by melting point, infrared, and proton nuclear magnetic resonance ( 1 H NMR) spectroscopy to be n-benzoyl GABA. Various parameters which influenced derivatization and elusion were optimized.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Therefore, these four compounds may be involved in the reduction of gold ions rather than other compounds (numbers 3, 5 and 6). 57,[60][61][62] The HPLC chromatogram also revealed that the percentage content of each identified compound is present in the extract. The high total percentage of carbonyl compounds is noticed as 77.115%, which is a higher percentage than compounds lacking carbonyl fragments (22.885%).…”
Section: Hplc Analysismentioning
confidence: 99%
“…Therefore, these four compounds may be involved in the reduction of gold ions rather than other compounds (numbers 3, 5 and 6). 57,[60][61][62] The HPLC chromatogram also revealed that the percentage content of each identified compound is present in the extract. The high total percentage of carbonyl compounds is noticed as 77.115%, which is a higher percentage than compounds lacking carbonyl fragments (22.885%).…”
Section: Hplc Analysismentioning
confidence: 99%